Overview of international research on indirect benefit and expense calculation methods: a bibliometric analysis (Research, Society and Development, 2020)
Markup is a percentage composed of indirect costs, profit estimates, and tax charges, applied to all services that make up the direct cost of a budget. However, this concept is the subject of debate due to differences in the determination of its components and calculation formulas. This article aims to identify the positions that differ from the composition of the markup, as well as the proposed calculation methods and the frequency of occurrence of the theme in the world scientific content. Through a bibliometric analysis, 42 relevant articles were identified that after the interpolation of the selected metadata resulted in 10 articles in which the difficulty in determining the markup is perceived, as well as alternatives for improving the conventional calculation process.